POTENSI INTERAKSI OBAT PADA PERESEPAN PASIEN GERIATRI RAWAT JALAN DI PUSKESMAS SATELIT BANDAR LAMPUNG TAHUN 2021 - Hijrah Hijrah; Lilik Koernia Wahidah; Ayu Herawati; Adityo Adityo (Program Studi Farmasi Universitas Tulang Bawang, 2022)
Drug interaction is the modification of the effect of a drug due to a drug being given alongside food, drinks or other drugs so that the effectiveness or toxicity of a drug changes. Some of the drugs prescribed in geriatric patients need to be considered so that no adverse drug interactions occur. This study aims to determine the potential for drug interactions in the prescribing of outpatient geriatric patients at the Bandar Lampung City Satellite Health Center in the 2021 period. This study is a non-experimental type with a descriptive design taken retrospectively. Sampling using purposive sampling method. The instruments in this study were medical records and prescriptions of geriatric patients, using the Drugs.com and Medscape applications. The results of this study showed that out of 256 prescriptions for geriatric patients there were 138 prescriptions (53.9%) who experienced drug interactions, with 120 male sex patients (46.9%) and female sex as many as 136 patients (53,1%). Based on the age category of 56-65 there were 110 patients (43%), aged 66-75 there were 120 patients (47%), and aged 76-90 there were 26 patients (10%). Drug interaction levels were minor category 51 patients (24.1%), moderate 140 patients (66.0%), and major 21 patients (9.9%). Based on the mechanism of pharmacodynamic interactions of 183 (86.3%) and pharmacokinetic interactions of 28 (13.7%). The conclusions of this study prove drugs administered to geriatric patients can cause drug interactions. Keywords : Drug Interactions, Geriatric, Prescription